Comparative Analysis of Household Debt Levels and Structures in European Countries: Trends and Implications - Małgorzata Grzywińska-Rąpca; Agnieszka Zawadzka (Ekonometria)
Aim: The aim of the article was to analyse the level and structure of household indebtedness in selected European countries over two periods: 2018–2019 and 2020–2022. The research focused on two key objectives: (1) a comparative analysis of the forms of indebtedness among households in different European countries, and (2) a comparative analysis of the euro area and non-euro area EU Member States with respect to the level and structure of household debt.